Intersystem Interference Study between Medical Capsule Camera Endoscopy and Other Systems in Co-Channel and Adjacent Bands - Shamsan, Z. A.; Almuhanna, K. (Engineering, Technology & Applied Science Research, 2021)
The Ultra-High Frequency (UHF) band occupies a very vital region in the spectrum and is becoming very congested because many applications use it. The capsule camera (CapCam), an ultra-low power wireless device, is a Short Range Device (SRD) application that utilizes the UHF spectrum for medical endoscopy and it is designed to operate at the 430-440MHz frequency band range. This study will focus on the interference between the CapCam and other systems operating in the frequency of 435MHz and adjacent bands. Other systems that can operate in this band include non-specific SRD and radiolocation services such as airborne radar and ground radar stations. The Minimum Coupling Loss (MCL) method is implemented in this study. The findings showed that restricted distances between the CapCam and other services must be considered when the CapCam is in use. This should be done to avoid harmful interference from the CapCam especially in the case of radiolocation services.